The effect of different teaching methods to understanding of chemical equilibrium at micro level [Kimyasal denge konusunun mikro boyutta anlaşılmasına farklı öğretim yöntemlerinin etkisi1] - Okumuş, S.; Çavdar, O.; Alyar, M.; Doymuş, K. (Ankara University, 2017)
The aim of this study is to determine students’ understandings related to chemical equilibrium at micro level by using different teaching methods. It was used quasi-experimental method with pre-and posttest. The sample was comprised of 90 first class science teacher education program students. It was studied with three groups: cooperative learning group (student teams achievement divisions method, STAD) (CLG, N=22), cooperative-model group (STAD + models) (CMG, N=41) and control group (CG, N=27). In order to compare the groups it was used a multiple choices Particulate Nature of Matter Test (PNMTa) related to chemical equilibrium. The PNMTa consists of six questions. For determining students’ conceptual understandings related to the subject, the PNMTa was rearranged as open-ended with removing choices (PNMTb). According to ANOVA results, it was not found significant difference among groups. Also, according to open-ended question, it was determined some misconceptions related to topic. © 2017, Ankara University. All rights reserved.
Keywords: Chemical equilibrium; Model; STAD; The particulate nature of matter